2014
DOI: 10.1037/a0033220
|View full text |Cite
|
Sign up to set email alerts
|

Belief in a just God (and a just society): A system justification perspective on religious ideology.

Abstract: Theoretical approaches that treat religiosity as an evolutionary byproduct of cognitive mechanisms to detect agency may help to explain the prevalence of superstitious thinking, but they say little about the social-motivational (or ideological) functions of religious beliefs or the specific contents of religious doctrines. To address these omissions, we develop the thesis that religion provides an ideological justification for the existing social order, so that prevailing institutions and arrangements are perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 97 publications
(124 reference statements)
13
127
0
4
Order By: Relevance
“…About 87.76% of the cognitive style scores in this study had moderation effects towards system justification. This study could offer an alternative explanation for findings conceived by Jost et al (2014), Uhlmann et al (2009) and Shenhav et al (2012). First, it affirmed the findings of Jost et al (2014) that emphasised a relationship between system justification and belief in God and found that there was no observed relationship between cognitive style and belief in God.…”
Section: Cssupporting
confidence: 60%
See 3 more Smart Citations
“…About 87.76% of the cognitive style scores in this study had moderation effects towards system justification. This study could offer an alternative explanation for findings conceived by Jost et al (2014), Uhlmann et al (2009) and Shenhav et al (2012). First, it affirmed the findings of Jost et al (2014) that emphasised a relationship between system justification and belief in God and found that there was no observed relationship between cognitive style and belief in God.…”
Section: Cssupporting
confidence: 60%
“…This study could offer an alternative explanation for findings conceived by Jost et al (2014), Uhlmann et al (2009) and Shenhav et al (2012). First, it affirmed the findings of Jost et al (2014) that emphasised a relationship between system justification and belief in God and found that there was no observed relationship between cognitive style and belief in God. Second, the results contradicted the predisposition coined by Uhlmann et al (2009) that belief in God is based on the implicit nature of intuitive thinking.…”
Section: Cssupporting
confidence: 60%
See 2 more Smart Citations
“…Religion and conservative politics are closely linked (Norris and Inglehart 2011) and research in the social psychological study of religion suggests that religion promotes system-justifying beliefs that enforce exclusionary moral boundaries, highlight individual responsibility over systemic causes of inequality, and reinforce the status quo (Edgell 2012;Jost et al 2014;Longest, Hitlin, and Vaisey 2013;Rankin, Jost, and Wakslak 2009). In other words, religious schemas tend to be oriented toward traditional moral values and conservative partisanship.…”
Section: The Underdog Paradoxmentioning
confidence: 99%